LEGAL ANALYSIS OF DIGITAL AGREEMENTS BETWEEN SELLER AND BUYER IN TRANSACTIONS-COMMERCE (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Advances in information technology have led to significant changes in the way people conduct buying and selling transactions, with digital agreements through e-commerce platforms becoming more commonplace. This study aims to evaluate the legality, binding force, and legal protection afforded to digital agreements between sellers and buyers in e-commerce transactions, in accordance with applicable Indonesian law. The method used in this study is normative juridical with a qualitative approach, emphasizing the analysis of laws and regulations such as the Civil Code (KUHPerdata), the Electronic Information and Transactions Law (UU ITE), and the Consumer Protection Law. The research findings indicate that digital agreements in e-commerce have the same legal force as traditional agreements provided they meet the requirements for a valid agreement, namely agreement, capacity of the parties, a clear object, and a legitimate cause. However, the implementation of digital agreements faces several challenges, such as issues of identity of the parties involved, electronic proof, and consumer protection from the risk of contract failure and fraud. Therefore, it is necessary to strengthen regulations, improve digital understanding, and develop adaptive dispute resolution mechanisms so that the principles of legal certainty and consumer protection can be optimally realized in digital transactions.